Pengaruh Variasi Mesh Karbon Aktif Dedak Padi Terhadap Massa Penyimpanan Biogas - Darma Wisnu, Pande Gede; Putra Negara, Dewa Ngakan Ketut; Sucipta, Made (Teknik Desain Mekanika, 2022)
Abstract Simantri is an interpretation of local agricultural development, especially for the Province of Bali which is moving towards a more integrated direction. The main activities of the simantri program include plant cultivation adapted to the characteristics of each region, utilization of plant waste as animal feed, and utilization of animal manure as compost and biogas Currently, the use of biogas is not evenly distributed, because the location of simantri as a biogas reservoir is uneven and for biogas distribution it requires the installation of pipes which are relatively expensive. This study is expected to determine the potential of using rice husk waste to become an adsorbent as a biogas storage medium using the ANG (Adsorbtion Natural Gas) system. The method used is the adsorption of biogas at a storage pressure of 100 psi with 70 grams of rice husk activated carbon as the adsorbent, the activated carbon was varied with a mesh size of 70-100, 100-200, and 200-500 at an activation temperature of 325oC. The results of the research in biogas storage showed that the highest mass absorption occurred in the variation of mesh 70-100 and mesh 200-500. Then for testing the biogas content, the highest levels of methane and the lowest carbon dioxide occurred at a mesh variation of 200-500. Keywords: rice husk, biogas, ANG, Carbon Active